Mandibular Canines with Two Roots and Two Root Canals: Case Report and Literature Review - Hugo Plascencia; Álvaro Cruz; Gerardo Gascón; Beatriz Ramírez; Mariana Díaz (Case Reports in Dentistry)
Usually, the mandibular canine only has one root and one root canal. However, there has been a noticeable increment in evidence showing variations in its morphology, such as the presence of two roots and two root canals. The aim of this article was to present a case of a mandibular canine with two roots and two root canals and to review the available literature on this anatomic variation. Root canal treatment of tooth #43 with such morphology was performed in a 47-year-old woman. Careful inspection of the preoperative radiograph indicated the presence of more than one canal. The 12-month follow-up showed normal periapical tissues, with no pain or tenderness. Literature review revealed that the overall prevalence of such root canal configuration is 5.7%, with a strong preference for female sex (87.5%). Although mandibular canines with two roots and two root canals are not common, clinicians should always anticipate the presence of possible variations. Therefore, timely diagnosis and meticulous exploration of such mandibular canines allow for planning of an individualized treatment protocol, tailored to their peculiar morphology, focused on avoiding excessive weakening or even perforation of the roots.